2017
DOI: 10.1177/0885066617712197
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sleep in the Intensive Care Unit: A Critical Appraisal of the Use of Subjective Methods

Abstract: Research using questionnaires to assess sleep is commonplace in light of practical barriers to polysomnography or other measures of sleep. A methodologically sound approach to tool development and testing is crucial to gather meaningful data, and this robust approach was lacking in many cases. Further research measuring sleep subjectively in ICU should use the Richards Campbell Sleep Questionnaire, and researchers should maintain a commitment to transparency in describing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
(80 reference statements)
2
27
0
Order By: Relevance
“…Decades of research have shown differences between sleep state perception and objectively measured sleep in a number of clinical sleep populations, most notably insomnia sufferers (80). A variety of patient completed questionnaires have been developed and used to assess perception of sleep in ICU and are covered by recent reviews (4,79). In this review, we focus on the most commonly used tools, and emphasize the validated ones such as the Richard Campbell Sleep Questionnaire (RCSQ), and the tools that were developed more recently.…”
Section: Patient Perception Of Sleep Using Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…Decades of research have shown differences between sleep state perception and objectively measured sleep in a number of clinical sleep populations, most notably insomnia sufferers (80). A variety of patient completed questionnaires have been developed and used to assess perception of sleep in ICU and are covered by recent reviews (4,79). In this review, we focus on the most commonly used tools, and emphasize the validated ones such as the Richard Campbell Sleep Questionnaire (RCSQ), and the tools that were developed more recently.…”
Section: Patient Perception Of Sleep Using Questionnairesmentioning
confidence: 99%
“…We evaluated the strengths and weaknesses of the measures, and their clinical and research usefulness. As an essential step, we assessed their measurement properties based on the criteria described by McDowell (3) and Jeffs and Darbyshire (4). Three aspects were critiqued: construct validity (i.e., whether the tool adequately and appropriately evaluated patient sleep?…”
Section: Introductionmentioning
confidence: 99%
“…Only one study used polysomnography to assess the sleep quality of five patients [21], while other studies used sleep questionnaires. However, sleep questionnaires, such as the Overran-Snyder-Halpern sleep scale, are not adequately validated in critically ill patients after comparison with polysomnography data [10]. To the best of our knowledge, there are no published studies assessing sleep quality of patients in Korean ICUs using the RCSQ, which is currently considered the most validated and reliable tool [10].…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported subjective assessments offer an alternative approach. Among the subjective tools, the Richards-Campbell Sleep Questionnaire (RCSQ) is the most validated and reliable tool [10]. The RCSQ consists of five questions assessing sleep depth, latency, and fragmentation, as well as time to the resumption of sleep and total sleep quality [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses use subjective techniques to determine sleep quality, such as a simple tool which allows its assessment. At present, there are a variety of self-assessment scales and questionnaires focused on quantifying and qualifying sleep quality and sleep disorders as well as on factors which have a significant negative effect on the sleep of ICU patients (Hoey et al, 2014;Jeffs and Darbyshire, 2017;Ritmala-Castren et al, 2016). The Richards-Campbell Sleep Questionnaire (RCSQ) is the most commonly used tool for evaluating subjective sleep quality in ICU.…”
Section: Introductionmentioning
confidence: 99%